One-Pot Synthesis of 5,6-Dihydro-4H-1,2-Oxazines by Cyclization of Ketoximes with Derivatives of Allylbenzene - Yahya, Raad Kasim; Rai, K. M. Lokanatha; Musad, Ebraheem Abdu; Sowmya, P. T. (JOURNAL OF ADVANCES IN CHEMISTRY, 2010)
A new series of 5,6-dihydro-4H-1,2-oxazines were synthesized via hetero Diels-Alder reaction ofÂ Î±-nitrosolefins with derivatives of allylbenzene. Î±-Nitrosoolefins were generated from ketoximes by the action of chloramine-T and triethylamine.